Re-conceptualizing information credibility in the age of networking society - Lai, Che Ching @ Abd Latif; Syahruddin Awg Ahmad; Cyril Modili (Penerbit UMS, 2020)
The main objective of this paper is to re-conceptualize the concept of information credibility. This is due to the fact that the current society, which is best labelled as ‘network society’ are becoming more complicated in relation to consuming information. The boundary of information producer and consumers are becoming thinner due to the advances in information technology. The existing body of knowledge about information credibility also warrant further investigation. Studies on information credibility are dispersed between the disciplines of communication, information technology and business studies. This has resulted in different conception of information credibility. Thus, this study was carried out using the Grounded Theory approach. There were four focus group discussions held to identify how the current society perceived information credibility. The choice of informants was based on the existing dialogue of digital natives and digital migrants. The finding shows that there is indeed new conception of information credibility. The concept of source and message are being strengthened, while two new concepts; ‘viral’ and ‘behaviour’ were added. The finding also reveals generational differences that warrant further investigation. The finding of this study is still open for further test due to the limitations of grounded theory approach.